Объяснение:
Коэффициент равен (У2-У1)/(Х2-Х1)=()()
Даны по две точки на каждой функции
(0;5 ) и (7,5;0) на первой (У2-У1)/(Х2-Х1)=(0-5)(7,5-0)=-5/7,5=-2/3
У=аХ+в; 0=-2/3*7,5+в; 0=-5+в; в=5
У=-2/3 Х+5
(-2;-1)(1;0 .)на второй. (У2-У1)/(Х2-Х1)=(0-(-1))(1-(-2))=1/3
У=аХ+в; 0=1/3*1+в; 0=1/3+в; в=-1/3
У=1/3 Х-1/3
Система уравнений
У=-2/3 Х+5
У=1/3 Х-1/3 *2
У=-2/3 Х+5
+
2У=2/3 Х-2/3 получим 3У=5-2/3 3у=4 1/3 У=13/9 У=1 4/9
1 4/9 = 1/3*Х -1/3 13/9 = 1/3*Х -3/9
16/9=1/3 Х
16/3=Х
5 1/3=Х ( 5 1/3; 1 4/9)
Объяснение:
a) 2*|x|-|x+1|=2
Модули уравнения равны нулю при х=0 и х-1=0 х=-1. ⇒
-∞____-1____0____+∞
x∈(-∞-1]
2*(-x)-(-(x+1))=2
-2x+x+1=2
-x=1 |÷(-1)
x=-1 ∈
x(-1;0)
2x-(-(x+1))=2
2x+x+1=2
3x=1 |÷3
x=1/3 ∉
x∈[0;+∞)
2x-(x+1)=2
2x-x-1=2
x=3 ∈
ответ: x₁=-1 x₂=3.
b) |x-2|+|x-3|+|2x-8|=9
|x-2|+|x-3|+2*|x-4|=9
Модули уравнения равны нулю при х-2=0 x=2, x-3=0 x=3, x-4=0 x=4.
-∞____2____3____4____+∞
x∈(-∞;2)
-(x-2)+(-(x-3))-2*(-(x-4))=9
-x+2-x+3-2x+8=9
-4x+13=9
4x=4 |÷4
x=1 ∈
x∈(2;3)
x-2+(-(x-3))+2*(-(x-4))=9
x-1-x+3-2x+8=9
-2x+10=9
2x=1 |÷2
x=0,5 ∉
x∈(3;4)
x-2+x-3+2*(-(x-4))=9
x-2+x-3-2x+8=9
3≠9 ∉
x∈[4;+∞)
x-2+x-3+2*(x-4)=9
x-2+x-3+2x-8=9
4x-13=9
4x=22 |÷4
x=5,5 ∈
ответ: x₁=1 x₂=5,5.
5(-0.3)(-0.3-0.5)+0.5(5(-0.3)+0.5)+0.5(-0.5+1)=0.45+0.75-0.75+0.25-0.25+0.5=0.95